The influence of Chinese architecture on traditional Melaka Mosques / Somayeh Armani - Somayeh, Armani (2014)
Since the sacred architecture manifests a clear reflection of each region's history, culture, and identity, the traditional mosques, as the symbols of Islamic art and architecture, always have intrigued countless architects and scholars worldwide. Although numerous materials have been documented about various mosques’ regional typologies, the Southeast Asian mosque architectural style has been surprisingly neglected. Since the advent of Islam in Southeast Asia during the 13th-15th centuries, innumerable traditional mosques with distinctive architectural form, constructional techniques, and ornamentation, very different from what is known as a mosque in Middle East and Central Asia, were erected in the region. Melaka, as the initial centre to disseminate Islam into Southeast Asia, holds valuable legacies, which are among the earliest mosques built in the area that remained intact, while represents a spectacular architectural style, with unique characteristics. Due to her special geographical location (located between great civilization of India and China), as well as her powerful role during the 15th -18th centuries, various ethnic groups from different cultures have been always attracted by Melaka, and influenced its architecture. Southeast Asia has been in a close connection with India since the beginning of Christian era, while Melaka has had a strong relation with China since the 15th century. As a result, Traditional Melaka mosque architecture shows foreign influences from great civilization of India and China, while is introducing an authentic style of indigenous Southeast Asian architecture. This study intends to identify the Chinese architectural influences on six selected traditional mosques in Melaka through employment of the Historical-Comparative Research method, by means of the historical and architectural literature, site observations, analysis, comparison, and interpretation. In this research, the Classical Chinese Architecture and Traditional Melaka mosque architecture have been explored and analysed, in order to provide the best feasible comparisons between Classical Chinese Architecture and selected case studies. This study focuses on architectural components of the roof, the façade, and the base from different aspects such as form, ornamentation, material and proportion. Through interpretation of the provided comparisons, this study indicates that the Chinese influences on Traditional Melaka mosques mostly occur in the ornamental means, the application of certain materials, the appearance of certain architectural elements, and to some extent in the proportions.